Perbandingan Latihan Kekuatan Resistance Band dan Dumbbell terhadap Hasil Shooting Jarak 6 Meter Cabang Olahraga Petanque - Lambok Gabriel Oktavianus; Yasep Setiakarnawijaya; Dadan Resmana (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This research aims to determine, 1) improvement in shooting technique through the resistance band training method, 2) improvement in shooting technique through the dumbbell training method, 3) calculation of improvement in shooting technique through the training method using resistance bands and dumbbells. The research method used in this research is an experiment with a quantitative approach and a Two Group Pretest Posttest Design research design. The subjects of this research were 30 Petanque athletes, students at SDN Rawamangun 09, taken using a purposive sampling technique. Data collection was carried out by conducting a shooting technique skills test at a distance of 6 meters using 1 target ball and 10 throws for each athlete. Data analysis was carried out using dependent and independent "t tests" with a significance level of 0.5. Research results: 1) training using Resistance Bands, obtained a t count of 6.2 which is greater than the t table of 2.145, so it means that H0 is rejected and H1 is accepted, meaning there is a significant increase, 2) training using Dumbbells, obtained a t count of 1.65 more smaller than the t table of 2.145, then H0 is accepted and H1 is rejected, meaning there is no significant improvement, 3) comparing the final test results of the two training methods, the results obtained are, t count 2.66 is greater than t table 2.048, meaning there is a difference between Resistance Band training method using Dumbbell exercises. So it can be concluded that there is a significant change in Resistance Band training with an average of 4.93 and Dumbbell training results with an average of 3.6.